Aplikasi Kompos Gulma Paitan (Tithonia Diversifolia) untuk Meningkatkan Pertumbuhan dan Hasil Kacang Hijau (Vigna Radiata L.) - Evita Evita; Jasminarni Jasminarni; Trias Novita (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to examine the effect of paitan compost in increasing the growth and yield of mung beans and to obtain a dose of paitan compost that provides the best growth and yield of green beans. The study was conducted at the Teaching and Research Farm, Faculty of Agriculture, Jambi University, 35 m above sea level. This study used a Randomized Block Design (RAK) with one factor, namely the provision of paitan weed compost consisting of 5 treatment levels, namely: p0 = fertilizer N , P and K recommendations, p1 = 7.5 tons ha-1 paitan compost, p2 = 15 tons ha-1 paitan compost, p3 = 22.5 tons ha-1 paitan compost, p4 = 30 tons ha-1 paitan compost. Each treatment was repeated 5 times. Variables observed were plant height, plant crown dry weight, weight (root dryness, number of pods per plant, seed weight per plant, weight of 1000 seeds yield ton ha-1). The results showed that the application of paitan weed compost had a significant effect on all variables. The application of Paitan weed compost at a dose of 30 tons ha-1 as a whole has been able to provide the best growth and yield of green bean plants